An Analysis of the Utilization of Health Operational Assistance Funds in Promotive and Preventive Programs at Sipatokkong Ogoamas Public Health Center - Megawati; Herlina Yusuf; Sriwahyudin Moonti (Yayasan Sinergi Kawula Muda, 2025)
Health Operational Assistance (HOA) funds are allocated for Public Health Center operations, and a minimum of 60% of the total allocation of the funds is used for Priority Health Programs through various highly leveraged activities to achieve MDGs goals in the health sector. A maximum of 40% of the funds is used for other Health Programs and Public Health Center Management. The method of this research is descriptive research using a qualitative research design. This research aimed to investigate the use of HOA funds at Sipatokkong Ogoamas Public Health Center. The results of this research show that the Public Health Center has allocated HOA funds following the technical guidelines that have been determined by utilizing the funds that are more focused on activities that will be prioritized at the Public Health Center, where the Public Health Center will see prioritized activities based on problems found first. The conclusion from the results of this research is that the use of HOA funds at the Siatokkong Ogoamas Health Center is following the technical guidelines that have been determined. The implementation of promotive and preventive health programs for MCH activities outside the building has yet to be carried out according to the planned schedule; achievement of target indicators for Minimum Service Standards at Sipatokong Ogoamas Health Center has yet to be achieved according to national standards.